The need for types of inpatient treatment and budget forecasting for lung cancer patients with a first established diagnosis - Yu. P. Yurkova; V. M. Merabishvili; E. V. Levchenko (Реальная клиническая практика: данные и доказательства)
Creating a disease models based on real-world clinical data from the moment of diagnosis is an important task of the healthcare system, it allows to simulate the quantitative need for hospitalizations with various options for necessary treatment and calculate the approximate amount of necessary funding.The study aims to build a model calculating the necessary volumes of medical care and funding for inpatient treatment of patients with lung cancer.Materials and methods. Anonymized data from the territorial compulsory medical insurance fund and the Department of high-tech medical care for all cases of lung cancer and metastases of any localization (ICD-10: C34 and C77-78) for residents of St. Petersburg, who received medical care from 2011 to 2020. Data from the population cancer registry database for all lung cancer patients in St. Petersburg since 2000.Results. More than 75 % of hospitalizations occur within 1 year from the moment of diagnosis: 68 % — chemotherapeutic treatment, 17 % — surgery, 3 % — radiotherapy. In the first year, 1 patient with stages I and II has an average of 2 hospitalizations, III and IV — 3. The calculated by the model number of hospitalizations in the 2 236 lung cancer patients in 5 years is 7 108. Payment for inpatient care based on the tariffs of the federal fund of 2022 and the number of newly diagnosed lung cancer diagnoses for five years will cost the healthcare system 1.1 billion RUR, and more than 74 % of this amount is the cost of 1 year of treatment. During the 5 years, surgery will cost 145 million RUR, chemotherapy — more than 898 million RUR, and radiotherapy — 37 million RUR.Conclusion. The developed on the real-world clinical data model can be used to calculate the necessary healthcare needs and its costs.